QAAPT: an interoperable web-based open-source tool for antimicrobial resistance data analysis and visualisation - Sujan, Mohammad Julhas; Gautam, Sanjay; Aboushady, Ahmed Taha; Clark, Adam; Kwon, Sooyoung; Joh, Hea Sun; Holm, Marianne; Stelling, John; Marks, Florian; Poudyal, Nimesh (Frontiers in Microbiology, 2025)
The analysis and visualisation of antimicrobial resistance (AMR) surveillance data is a crucial challenge, especially in high-burden, low-middle-income countries. We describe the design, development, integration, and implementation of the Quick Analysis of Antimicrobial Patterns and Trends (QAAPT) tool for AMR data analysis and visualisation. The QAAPT tool was created by the Capturing Data on Antimicrobial Resistance Patterns and Trends in Use in Regions of Asia project, led by the International Vaccine Institute (IVI). This open-source web-based tool/application generates statistical and visual outputs of AMR data, offers data curation options, and can be integrated with laboratory information management systems. The QAAPT tool is user-friendly and is operable by someone with limited expertise in software or programming. As a part of the project, the tool was used to analyse data from 72 laboratories across 7 Asian countries. In this study, we present the technical aspects of tool development and highlight implementation outcomes for analysing and generating visual reports from more than 2.37 million highly heterogeneous antimicrobial susceptibility test data points.